Niger : Assessment Letter for the World Bank and the European Union. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Niger's macroeconomic performance in 2010 was strong, mainly reflecting the exceptional 2010-11 harvest. The bumper crop and the completion of the year-long transition to democracy have also brightened the near-term economic outlook. The recently-adopted revised 2011 budget foresees an increase in expenditure financed in large part by the expected pick-up in external support, helped by the freeing up of resources as ill-targeted fuel price subsidies are gradually phased out. The authorities have expressed a wish to initiate discussions on an economic program that could be supported by the Fund under the Extended Credit Facility in the coming months.a.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Niger